IMPLEMENTATION OF RESTORATIVE JUSTICE BY PROBATION AND PAROLE OFFICERS IN INDONESIA - Wahyu Saefudin; Nasirudin Nasirudin (Polteknik Ilmu Pemasyarakatan, 2022)
The cases enforcement of children in conflict with the law has shifted from retribution to restorative. This policy transformation was in line with the ratification of Act 11/2012 on the Juvenile Criminal Justice System, which replaced Act 3/1997 on Juvenile Court. This study aims to examine the role of community mentors in Indonesia, both before and after implementing the Juvenile Criminal Justice System Act. This study utilizes a qualitative approach through literature review with primary data originating from legislation, scientific journals, and books then studied systematically and described descriptively. The study results explain that probation and parole officers have a significant role in implementing restorative justice in Indonesia. This role has been proven to reduce the number of child criminals who must end up in prison. This study shows differences in the number of prison sentences for children before and after the enactment of the Juvenile Criminal Justice System Act. Probation and parole officers are at the forefront of implementing restorative justice in Indonesia through their duties and functions